eQTL-driven tissue-specific modulation by TMPRSS2 (rs12329760) and its potential role in COVID-19 susceptibility - Sokolenko, Maksym; Sydorchuk, Larysa (ScienceRise: Medical Science, 2025)
The aim of research – to analyze tissue-associated expression of the TMPRSS2 gene (rs12329760) using quantitative expression loci and assess its potential contribution to the formation of individual susceptibility to COVID-19. Material and methods. Genotyping of TMPRSS2 (rs12329760) was performed for 48 patients with mild COVID-19 and 72 patients with moderate and severe disease. Peripheral blood leukocytes were used to isolate genomic DNA, and real-time polymerase chain reaction was used to genotyping gene polymorphisms. eQTL analysis was applied based on publicly available data from the QTLbase database to establish tissue-specific transcriptional effects of the TMPRSS2 variant (rs12329760). Results. It was found that TMPRSS2 (rs12329760) showed the highest number of transcripts in prostate tissue. A total of 80 eQTLs associated with rs12329760 were identified, all of which were driven exclusively by cis-regulatory mechanisms, with these associations distributed across 19 tissues and involving regulatory interactions with 18 genes. The T allele of rs12329760 was associated with significantly increased expression of MX1, MX2, and AP001610.1 in CD4⁺ T lymphocytes, circulating monocytes, and B lymphocytes. In contrast, the C allele was associated with increased expression of FAM3B and BACE2 in CD16⁺ neutrophils and CD14⁺ monocytes. Opposing regulatory effects were also found: rs12329760 was associated with transcriptional suppression of C2CD2, PRDM15, TMPRSS3, and UMODL1 in CD4⁺ T cells and B lymphocytes, predominantly mediated by the T allele. Conclusions. The TMPRSS2 gene (rs12329760) has broad tissue-specific regulatory activity, enhancing the expression of genes involved in the formation of the human antiviral response, while involving mechanisms related to the complement system and serine protease. These transcriptional effects suggest that rs12329760 may serve as a functional modifier of susceptibility and immune response in COVID-19